An integrated system of applying the use of Internet of Things, RFID and cloud computing: A case study of logistic management of Electricity Generation Authority of Thailand (EGAT) Mae Mao Lignite Coal Mining, Lampang, Thailand - Chieochan O. (2017)
© 2017 IEEE. This research aims to find the best practice of logistic management for Electricity Generation Authority of Thailand (EGAT) Mae Mao Mining, Lampang. This research applied the use of RFID for lignite coal trucks and data from RFID proceed through a server and was stored into a private cloud computing. The equipment and tools used in research was a RFID reader, UHF passive RFID tags, Arduino Mega 2560 + Ethernet Shield, PHP, Jason, Node.JS and Maria DB as a database system. The protocol used was MQTT. 27 trucks had UHF passive tags installed, 1 crusher (location number 3) had an RFID reader installed. This system has been operating 24 hours a day 7 days a week, from the beginning of 2015 to mid 2016. The results of the research show that officers who worked for related systems were satisfied. The system enhanced the best practice of lignite coal mining logistic in terms of information checking.